Physicochemical characterization of Annona muricata L., fruits in Junin, Peru - Paitan, Elizabeth; Marmolejo, Doris; Marmolejo, Karina; Huamán, Edith (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Soursop (Annona muricata L.) is an exotic fruit with high international demand, valued for its flavor, nutritional properties, and applications in the food industry. In Peru, its use includes fresh consumption and the production of pulp, nectars, and nutraceutical products. The objective of this study was to evaluate the physicochemical characteristics of fruits from selected soursop plants grown at the San Ramón Agricultural Experimental Station in the Department of Junín, Peru. The physical characteristics (fruit mass, polar and equatorial diameter), chemical characteristics (titratable acidity, ionic acidity, total soluble solids, and maturity index), as well as mineral content (phosphorus, magnesium, and calcium) were determined from the fruits. A completely randomized experimental design (CRD) and analysis of variance (ANOVA) were applied. The results showed that the FRCUNCP_09 and FRCUNCP_12 genotypes had the largest fruit mass (2.49 and 2.16 kg, respectively). On the other hand, the FRCUNCP_08, FRCUNCP_09, and FRCUNCP_12 genotypes presented optimal values of titratable acidity (0.8367, 0.9900, 1.1133), ionic acidity (3.99, 4.16, 3.62), and total soluble solids (16.5, 15.9, 17.7 BRIX), suitable for direct consumption and industrial processing. Regarding mineral content, FRCUNCP_09 had the highest concentrations of phosphorus (23,135 mg.100 g-1) and calcium (6,200 mg.100 g-1), while FRCUNCP_08 stood out for its magnesium content (21,604 mg.100 g-1). It is concluded that these materials have potential for genetic improvement programs and the development of nutraceutical products.